Investigating the impact of process parameters on the thermomechanical properties of three-dimensional (3D) printed polymer-nanoclay composites - Sheymaa Alazzawi; Noor Hassan Ali; Suha K. Shihab; Muammel M. Hanon (International Journal of Thermofluids)
The additive manufacturing of polymer-nanoclay composite systems has been of great interest in developing material systems that are lightweight, tough, and thermally stable. However, attaining maximum thermomechanical properties in three-dimensional (3D) printed composite is challenging given the complex interactions between processing parameters and material structure. This work meets the challenge by investigating the novel use of montmorillonite nanoclay in a plant-based photopolymer resin for Digital Light Processing (DLP) -based three-dimensional (3D) printing applications. The objectives of this work were to improve the thermal conductivity, tensile strength, flexural strength, and impact resistance of the composite, and optimize key processing parameters such as nanoclay concentration, printing orientation, and layer thickness using Response Surface Methodology (RSM). The results of this work indicate that a nanoclay concentration of 0.4496 wt.%, a printing orientation of 61.18°, and a thickness of 0.03 mm produce the maximum thermomechanical properties of the composite. The optimal composite exhibited excellent properties, recording a tensile strength of 48.93 MPa, a flexural strength of 63.31 MPa, a thermal conductivity of 0.3296 W/m·K, and a maximum impact energy of 0.3275 J. The results of this work mark a great milestone in the field given the great potential of using environmentally friendly, plant-based composite systems in high-performance applications such as functional prototypes, medical models, and complex industrial components. The work not only presents a strategic approach to improving 3D-printed polymer-nanoclay composite material systems but also enhances our in-depth knowledge of process-structure-property relationships in additive manufacturing processes.